191k views
0 votes
Solve the system by elimination

Solve the system by elimination-example-1
User Dan Me
by
6.2k points

2 Answers

3 votes

Answer:

x= -2 y= -5

Explanation:

Eliminate y by subtract = 3x-6x-2y+2y=6 ; x=-2

plug-in x = -2

-6-2y = 4 y = -5

User Lukemh
by
6.2k points
4 votes

Answer:

(- 2, - 5)

Explanation:


\left \{ {{3x-2y=4} \atop {6x-2y=-2}} \right.

(2) - (1)

(6x - 3x) + [- 2y - (- 2y)]= - 2 - 4

3x = - 6 ⇒ x = - 2

3( - 2) - 2y = 4 ⇔ - 6 - 2y = 4 ⇒ y = - 5

(- 2, - 5)

User Jannah
by
6.2k points